Fragmentation des habitats et le devenir des lémuriens du Sud et du Sud-ouest de Madagascar - Germain Jules Spiral; Soanorolalao Ravelonjanahary (Revue de Primatologie)
Once called "green island", Madagascar is now one of the most degraded part of the world due to all kinds of human activities. Since men arrived on the island, progressive degradation of forests became more and more alarming for the survival of lemur populations as well as the whole nation, particularly in the southern and south western regions leading to the handicap of the development of the country. Therefore, urgent rules of conservation and preservation must be undertaken as priority in the region or even in the country in order to limit at least partially the observed degradations and insure a better future for the next generations.